MOTIVASI IBU TERHADAP PEMBERIAN MAKANAN TAMBAHAN PADA BAYI USIA 6-9 BULAN DI PUSKESMAS TAMBAKREJO KABUPATEN JOMBANG - Fatimah, Siti; Stianto, Mitayakuna (WELL BEING, 2020)
One of the factors thatiican causeiimalnutrition iniichildren underiifive are the bad behavior of the mother in providing food assistance to their children breast milk, so the children do not get enough nutrients for growth and development. Theiaim of researah to determineiithe effectiiof motivation and attitudes of mothers towards supplementary feeding behavior in infants aged 6 months in health Tambakrejo Jombang. The study designiwas observationaliiwith cross sectionaliiapproach. Respondentsiiwere drawn by simpleirandom samplingitechnique. PopulationiAll mothers ofichildren aged 6-9 months were 63 people, a sampleiiof 51 respondents. The independentiivariable of motivation and attitudes, behaviors dependent variable supplementary feeding, and then analyzed using logisticiiregression statistical test. The resultsiishowed most respondents are motivated to give breastfeeding categories were as many as 32 (62.7%) of respondents, most respondents have the attitude to giving breastfeeding with negative category as many as 31 (60.8%) respondents, and almost a half of respondents have a behavior in the provision of breastfeeding by category quite as many as 23 respondents (45.1%) of the total 51 respondents. Data analysis results show the value of p - value = 0.001 to influence the motivation of the behavior andiithe provision of breastfeeding p - value = 0,029 to influence attitudes towards the provision of breastfeeding behavior <α 0,05 so H1iiaccepted whichiimeans thereiiis influenceiiof motivation and attitudes of mothers towards supplementary feeding behavior in infants aged 6-9 months in health Tambakrejo Jombang. High motivation may encourage mothers to exclusively breastfeed, as well as positive attitudes will encourage mothers to exclusively breastfeed because mothers assume that exclusive breastfeeding is good for the baby.